Revisiting Practical Wisdom: A Reinterpretation of Ḥikmah Muta‘āliyah in Political Thought - Muhammad Rahim (Talenta Publisher, 2026)
Philosophy is often reduced to a static enterprise of systematizing inherited traditions, losing its fundamental role in re-interpreting reality. In the context of Islamic thought, Ḥikmah Muta‘āliyah—despite its core principle of